2008
DOI: 10.1007/s12127-008-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Exemplar application of multi-capillary column ion mobility spectrometry for biological and medical purpose

Abstract: In recent years, ion mobility spectrometry is increasingly in demand for new applications especially on biological samples (cells, bacteria, fungi), in medicine (diagnosis, therapy and medication control e.g. from breath analyses), for food quality control, safety monitoring and characterisation or process control in chemical and pharmaceutical industry. For this purpose instruments based on gas phase separation of ions in weak electric fields were developed at ISAS-Institute for Analytical Sciences, focussing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 26 publications
(33 reference statements)
0
43
0
Order By: Relevance
“…For details see [41]. Details considering the MCC/IMS are summarised in [38]. Temperature and pressure fluctuations in the drift tube and alignment of spectra are considered in [42].…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…For details see [41]. Details considering the MCC/IMS are summarised in [38]. Temperature and pressure fluctuations in the drift tube and alignment of spectra are considered in [42].…”
Section: Measurementmentioning
confidence: 99%
“…Figure 1 shows a cut-out of a typical IMS-Chromatogram of an air sample simulating human breath (for experimental details see [30][31][32]38]). Normally, a visualisation is realised by clicking into the 2D-plot in window A to get the corresponding single spectrum in window B for rather visual inspection.…”
Section: Introductionmentioning
confidence: 99%
“…a human breath analysis using an ion mobility spectrometer equipped with a Multi-CapillaryColumn (MCC) should be considered. The resulting data set consists of a set of parameters describing the whole measurement and experimental setup and of a set of single spectra at different retention times-for further experimental details see ref [35][36][37][38][39][40][41][42][43]. The origin of the data could be DMS, FAIMS or other IMS-it is only essential to have such structured information available.…”
Section: Visualisationmentioning
confidence: 99%
“…Thermogravimetric assessment combined with headspace analysis by ion mobility spectrometry and gas chromatography-mass spectrometry indicated that Zeonex TM encapsulated carbon-loaded nylon could be used to fabricate a snaptogether injection molded stacked ring drift tube, 4.25 cm long that could be substituted for a conventional wire-wound heated ceramic drift tube of the same length into a high temperature ion mobility spectrometer. 3,4 ; food quality and environmental 5 screening applications 6,7 . Another vitally important aspect of IMS is the continuing development of IMS-MS systems and applications, and a recent review provides a useful and informed overview of this area 8 .…”
Section: Introductionmentioning
confidence: 99%